Komparasi Hukum Pada Fatwa Cryptocurrency di Malaysia dan Timur Tengah - Makraja, Fahmi; Mirza Al Fajri (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2024)
Abstract Cryptocurrency is a digital currency that is used as a means of exchange for online transactions. The use of Cryptocurrency has become a hot issue in the world, considering the significant current of change in digital technology, so an in-depth study regarding Cryptocurrency law is very necessary. This research discusses legal comparisons on Cryptocurrency fatwas in Malaysia and the Middle East. The aim of this research is to analyze and compare the legal status of Cryptocurrency fatwas in Malaysia and the Middle East. The method used in this research is a comparative juridical approach. The research results show that there are differences between Cryptocurrency fatwas in Malaysia and the Middle East, these differences are based on different legal reasons. In Malaysia, a study of sharia law explains that Cryptocurrency does not meet the criteria as a currency. In Egypt, the use of Cryptocurrency has the potential to damage the economic order considering that the transaction exchange medium used is not in accordance with Sharia law. In Pakistan, Cryptocurrency is against the terms of money set by FATT. In Saudi Arabia, Cryptocurrency opens up opportunities for illegal transactions and is contrary to Islamic economic rules. And Iran, Ayatollah Ali Khamenei's group gave a signal that it would allow the use of Cryptocurrency, but other groups opposed the use of Cryptocurrency as a medium of exchange or commodity. Keywords: Cryptocurrency, Malaysian Fatwa, Middle East